2019
DOI: 10.21608/zvjz.2019.6484.1017
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Virulence and Antibiotic Resistance Genes in Pasteurella multocida Isolated from Diseased Rabbits

Abstract: Pasteurella multocida (P. multocida) is considered a predominant pathogenic bacterial agent causing respiratory manifestations (snuffles) in rabbits with considerable economic losses and unfavorable prognosis in Egypt. A few recent P. multocida strains exhibit resistance to the most commonly used antibiotics in the veterinary field. Therefore, the present study was carried out to investigate the prevalence of both virulence and antibiotic resistance genes among P. multocida isolated from diseased rabbits in Sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Records of bla CTX-M and bla CTX-M-1 in P. multocida isolates from cattle and humans, either healthy or diseased, are few in Egypt, so this may be the first report confirming the existence of these ESBL genes in P. multocida isolates from cattle and human sources in Egypt. However, the published results from Egypt by Awad et al [ 56 ] and Elalamy et al [ 57 ], confirmed the presence of bla ROB-1 in 20% of the P. multocida isolates from diseased rabbits and 8.3% from diseased chicken, respectively. TEM-1 is able to hydrolyze penicillin and the early cephalosporins; its existence in the P. multocida isolates of human origin was reported by Naas et al [ 58 ], and from cattle by Michael et al [ 54 ], who confirmed that the presence of TEM-1 in P. multocida is of veterinary importance.…”
Section: Discussionmentioning
confidence: 95%
“…Records of bla CTX-M and bla CTX-M-1 in P. multocida isolates from cattle and humans, either healthy or diseased, are few in Egypt, so this may be the first report confirming the existence of these ESBL genes in P. multocida isolates from cattle and human sources in Egypt. However, the published results from Egypt by Awad et al [ 56 ] and Elalamy et al [ 57 ], confirmed the presence of bla ROB-1 in 20% of the P. multocida isolates from diseased rabbits and 8.3% from diseased chicken, respectively. TEM-1 is able to hydrolyze penicillin and the early cephalosporins; its existence in the P. multocida isolates of human origin was reported by Naas et al [ 58 ], and from cattle by Michael et al [ 54 ], who confirmed that the presence of TEM-1 in P. multocida is of veterinary importance.…”
Section: Discussionmentioning
confidence: 95%
“…Overall, fairly low levels of resistance were reported in P. multocida isolates. For penicillins , one study from Egypt reported that all of 10 included isolates were resistant to both ampicillin (included as a surrogate for penicillin/amoxicillin, used only by the parenteral route in rabbits) and amoxicillin–clavulanic acid (Awad and Abd El‐Hamid, 2019 ). Another study from Brazil (Ferreira et al, 2012 ) found 10.9% and 6.5% of 45 isolates resistant to penicillin and amoxicillin, respectively, whereas a Chinese study found all 205 included isolates susceptible to penicillin (Wang et al, 2019 ).…”
Section: Assessmentmentioning
confidence: 99%
“…In addition, Tang et al (2009) provided the new epidemiological information on the prevalence and distribution of virulence factors of P. multocida isolates. Kim et al (2019), Awad & Abd El-Hamid (2019), and Aski & Tabatabaei (2016) found that the prevalence of some VAGs encoding adhesin factors (ptfA, fimA, hsf-1, hsf-2, pfhA, tadD), toxin (toxA), sialidase factors (nanB, nanH), and outer membrane proteins (ompA, ompH, oma87, plpB, psl) in P. multocida isolates from diseased swine, rabbits, poultry and other animals. We also investigated the presence of 23 virulence genes in 9 isolates in this study.…”
Section: Investigation Of Genetic Diversity Of Pasteurella Multocida ...mentioning
confidence: 99%